2003
DOI: 10.1002/mrm.10366
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of effects of mean arterial blood pressure induced by cocaine and cocaine methiodide on BOLD signals in rat brain

Abstract: A total of 45 male Sprague-Dawley rats were employed to determine whether cocaine or cocaine methiodide (CM) administration can induce a significant increase in mean arterial blood pressure (MABP) in rats, and whether such an increase in MABP can produce a global increase in blood oxygenation level-dependent (BOLD) contrast in the rat brain detectable by functional magnetic resonance imaging (fMRI). Cocaine methiodide is a quaternary derivative of cocaine that shares the same cardiovascular effects of cocaine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 21 publications
8
44
0
Order By: Relevance
“…Whether temporal correlations observed between the time series from different brain regions truly reflect correlation between neural activity rather than correlation between drug-induced changes in cerebral blood flow remains difficult to be certain. However, it has been shown that the shape of the hemodynamic response that is used to estimate effects in fMRI studies is not altered by drugs known to have vascular effects (Gollub et al, 1998;Luo et al, 2003;Murphy et al, 2006). Furthermore, even if the effects of delta-9-THC and/or CBD on global cerebral blood flow were to have influenced the results of the connectivity analysis, such effects would not have been localized to specific brain regions as observed here.…”
Section: Limitationsmentioning
confidence: 72%
“…Whether temporal correlations observed between the time series from different brain regions truly reflect correlation between neural activity rather than correlation between drug-induced changes in cerebral blood flow remains difficult to be certain. However, it has been shown that the shape of the hemodynamic response that is used to estimate effects in fMRI studies is not altered by drugs known to have vascular effects (Gollub et al, 1998;Luo et al, 2003;Murphy et al, 2006). Furthermore, even if the effects of delta-9-THC and/or CBD on global cerebral blood flow were to have influenced the results of the connectivity analysis, such effects would not have been localized to specific brain regions as observed here.…”
Section: Limitationsmentioning
confidence: 72%
“…Of note, in an fMRI study performed at 4.7 T, Spenger et al (2000) also report highly variable activations outside the somatosensory pathway (with no changes in MABP and HR) during forepaw stimulation in rats under α-chloralose anesthesia previously optimized to eliminate pain response to electrical stimulation. Second, isoflurane also depresses cerebrovascular reactivity to CO 2 relative to awake conditions (Sicard et al, 2003) which may explain the stronger hypercapnic challenges required to derive M. In animal studies, 5% and 10% CO 2 challenges are commonly used with other anesthetics (Luo et al, 2003;Wu et al, 2002), and the former is frequently used in human studies (Davis et al, 1998;Hoge et al, 1999). Third, isoflurane is a cerebrovasodilator which increases basal CBF (Hendrich et al, 2001;Matta et al, 1999), thus potentially reducing the head room for forepaw stimulation-or hypercapnia-evoked CBF and/or BOLD increases.…”
Section: Potential Drawbacks Of the Isoflurane-anesthetized Forepaw-smentioning
confidence: 99%
“…Another implication is in pharmacological fMRI. Following drug administration, for example, the baseline physiological state of the brain could be different regionally or globally due to drug-induced changes in respiration rate, blood pressure and/or volume, and vascular tone (Luo et al, 2003). These alterations, which are independent of the drug-induced changes in neural activity, could markedly affect the relative stimulus-evoked fMRI signals.…”
Section: Implications To Fmri Studies That Measure Relative Cbf and Bmentioning
confidence: 99%
“…For example, using 0.7% halothane, 1 mg/kg cocaine was found to elicit widespread increases in regional CBV using contrast and functional MRI (fMRI) (Marota et al, 2000). In another study, urethane was used as an anesthetic, and cocaine was found to cause widespread and dosedepended early decreases and later increases in the blood oxygenation level-dependent (BOLD) fMRI signal with intravenous cocaine challenges in the rat brain (Luo et al, 2003). Recently, isoflurane-anesthetized rats were used, and intravenous cocaine (1 mg/kg) was found to elicit a negative BOLD fMRI signal on the cortical surface (Schmidt et al, 2006), which is especially relevant for our study because our optical probe only records changes in the cortical surface (1-2 mm) (Du et al, 2005).…”
Section: The Effects Of Cocaine On Cbv and S T Omentioning
confidence: 99%